2002
DOI: 10.1017/s0305000902005020
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of compound vs. phrasal stress: the role of prosodic constituents

Abstract: This paper investigates the acquisition of compound vs. phrasal stress (hót dog vs. hot dóg) in English. This has previously been shown to be acquired quite late, in contrast to recent research showing that infants both perceive and prefer rhythmic patterns in their own language. Subjects (40 children in four groups the averages ages of which are 5;4, 7;2, 9;3 and 11;6 and 10 adults) were shown pairs of pictures representing a compound word and the corresponding phrase. They heard a prerecorded tape with the n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
57
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(66 citation statements)
references
References 13 publications
8
57
1
Order By: Relevance
“…Cruttenden (1974) found that the ability to use stress to infer semantic contrast does not fully develop until between 7 and 10 years of age. Holdgrafer and Campbell (1986) found a similar developmental delay in the ability to infer that accent marks new rather than given information, and a recent study by Vogel and Raimy (2002) showed that not until age 11 can children use stress patterns to distinguish between pairs of words used as adjective-noun phrases vs. adjective-noun compounds (e.g. hot dog vs. hotdog).…”
Section: Discussionmentioning
confidence: 79%
“…Cruttenden (1974) found that the ability to use stress to infer semantic contrast does not fully develop until between 7 and 10 years of age. Holdgrafer and Campbell (1986) found a similar developmental delay in the ability to infer that accent marks new rather than given information, and a recent study by Vogel and Raimy (2002) showed that not until age 11 can children use stress patterns to distinguish between pairs of words used as adjective-noun phrases vs. adjective-noun compounds (e.g. hot dog vs. hotdog).…”
Section: Discussionmentioning
confidence: 79%
“…Vogel and Raimy (2002) reported that single nouns and initial compound constituents differ systematically in their prosody (mean duration and mean fundamental frequency). In the series of experiments described by Isel et al (2003) it was suggested that the durational difference between single nouns and initial compound constituents can delay the semantic processing of initial compound constituents.…”
Section: Introductionmentioning
confidence: 99%
“…Finally she shows that, if we accept the Clitic Group, the interpretation of the psycholinguistic experiments with Dutch speakers becomes quite simple, providing psycholinguistic motivation for the proposals suggested by her paper. Incidentally, Vogel and Raimy (2002) also suggest that the Clitic Group is needed to describe the difference between compound stress in English (which takes the Clitic Group as its domain), and phrasal stress (which is based on the Phonological Phrase domain). They suggest that the Clitic Group might be renamed "Composite Group", which allows us to maintain the relatively flat structure of phonology compared to morpho-syntax.…”
Section: Part 1 Prosodic Hierarchy and The Nature Of Prosodic Constimentioning
confidence: 99%